2021
DOI: 10.48550/arxiv.2104.02156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unified Detection of Digital and Physical Face Attacks

Abstract: State-of-the-art defense mechanisms against face attacks achieve near perfect accuracies within one of three attack categories, namely adversarial, digital manipulation, or physical spoofs, however, they fail to generalize well when tested across all three categories. Poor generalization can be attributed to learning incoherent attacks jointly. To overcome this shortcoming, we propose a unified attack detection framework, namely UniFAD, that can automatically cluster 25 coherent attack types belonging to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Solutions of the unimodal (colour) track: Table 8 summarizes the face PAD solutions of the teams participated in the unimodal track. The source codes of ten teams, including VisionLabs 10 , BOBO 11 , Harvest 12 , ZhangTT 13 , Newlandtianyan 14 , Dopamine 15 , IecLab 16 , Chungwa-Telecom 17 , Wgqtmac 18 , and Hulking 19 were made publicly available. It was not surprising that every team adopted end-toend learning based approaches due to the strong representation capacity of modern deep models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solutions of the unimodal (colour) track: Table 8 summarizes the face PAD solutions of the teams participated in the unimodal track. The source codes of ten teams, including VisionLabs 10 , BOBO 11 , Harvest 12 , ZhangTT 13 , Newlandtianyan 14 , Dopamine 15 , IecLab 16 , Chungwa-Telecom 17 , Wgqtmac 18 , and Hulking 19 were made publicly available. It was not surprising that every team adopted end-toend learning based approaches due to the strong representation capacity of modern deep models.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the differences in generation techniques and visual quality, some of these attacks still have coherent properties and artefacts. In [13], a unified digital and physical face attack detection framework is proposed to learn joint representations for coherent attacks. Therefore, another interesting challenge to tackle in upcoming contests as-sessing the robustness of face biometric systems would be to simultaneously detect both digital and physical attacks.…”
Section: Future Challengesmentioning
confidence: 99%
“…In contrast to hardware-based methods, software-based techniques have been proposed to spot attacks in the physical and digital domain. In general, the existing detection schemes use i) texture analysis [13], ii) digital forensics [23], or iii) deep-learning techniques [14], [11].…”
Section: Related Workmentioning
confidence: 99%
“…Mehta et al [25] proposed an algorithm that showed promising detection results on three PAI species in the physical domain (silicone mask, photo-, and video-replay attacks) and one attack in the digital domain (face swap). In [11], Deb et al proposed a multi-task learning framework with k-means clustering, which showed high detection accuracy (∼94.73%) on a database comprising 25 attack types across three different attack categories (adversarial, digital, and physical).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation